Pengaruh Tipologi Arsitektur Kawasan Pariwisata Kota Bandung terhadap Ketidakmerataan Tingkat Minat Pengunjung - Ahmad Bayhaqi; Andhika Ahmad Argiansyah; Aliyuddin Muhammad; Daffa Hilman Anshory; Rama Wijaya Abdul Rozak (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Bandung is one of the most popular tourist destinations in Indonesia and offers a wide variety of architectural styles and types. Although Bandung offers many different architectural styles that attract tourists, unfortunately not all tourist attractions in Bandung offer the same experience in discovering the beauty of the existing architecture. The purpose of this research is to improve the quality tourism attraction and experience of tourist attractions in Bandung by focusing on aspects such as comfort, safety, and accessibility. With the aim to create unique and memorable buildings in the long term, such as building facades, to maintain tourists' interest and encourage more tourists to visit the area regularly. In addition, to investigate how architectural features affect tourism in Bandung City by using qualitative descriptive method to increase tourists' interest. Data was collected through a qualitative open-ended questionnaire from aged respondents who live in Indonesia and have visited Bandung city. The results showed that most respondents were very satisfied with their tourism experience in Bandung City, with the majority visiting tourist attractions to seek new experiences or for healing purposes. The majority of respondents also found it easy to find information about tourist attractions in Bandung and recommended Bandung as a tourism destination to others. However, there were still some respondents who were dissatisfied with public facilities at tourist attractions, such as cleanliness and comfort, as well as the management of rundown tourist spaces.